Optimal design of bridge columns constructed with engineered cementitious composites and Cu-Al-Mn superelastic alloys. (1st November 2019) - Hosseini, Farshid; Gencturk, Bora; Jain, Amit; Shahzada, Khan
Highlights: High fidelity modeling of bridge columns with high-performance materials under seismic loading. Modeling and calibration of fiber-reinforced cementitious composites and superelastic alloys for continuum modeling. Parametric study to determine the optimal use of high-performance materials. Demonstration of effective column designs with high seismic resiliency. Abstract: Recent major earthquakes have shown that conventional bridge columns are susceptible to large residual deformations and considerable damage to the plastic hinge region under seismic loading. The use of high-performance materials such as high-performance fiber reinforced concrete (HPFRC) and superelastic alloys (SEA) has attracted attention in the recent years to address these issues. Unique properties of engineered cementitious composites (ECC), as a special type of HPFRC, including superior ductility and durability compared to conventional concrete and non-localized multiple fine cracking under cyclic tensile loading have been shown to improve the damage tolerance of bridge columns. Moreover, the ability of SEAs to recover large inelastic deformations, when replaced with traditional steel reinforcement, significantly reduces the permanent deformations in bridge columns subjected to ground shaking. The objective of this study is to identify the optimal geometry and material distribution of an innovative bridge column concept that has recently been demonstrated to be effective in addressing these issues, i.e., damage tolerance and post-earthquake functionality. A numerical parametric study of high-fidelity full-scale bridge column models incorporating ECC and Cu-Al-Mn (CAM) SEA bars has been performed. The material properties of ECC, the thickness of the hollow reinforced ECC (RECC) column cross-section, the number of CAM SEA bars in the plastic hinge region, and the effect of a concrete core have been investigated as the variables of the parametric study. It was found that the ductility of ECC in tension had little influence on the global behavior of the columns, the hollow columns up to a hollow ratio of 35% performed equally well as the solid ones, and there was an optimal replacement ratio of approximately 65% of the steel reinforcement with CAM SEAs that would yield a compromise between energy absorption and self-centering capacity.